The First Amendment, Varieties of Neutrality, and Same-Sex Marriage - Gill, Emily R. (Politics and religion, 2009)
This article compares the difficulty in achieving a public stance of neutrality toward sexual orientation with the difficulty in achieving neutrality toward religious belief. Strict separation treats religion as a private commitment, with firm limits on government cooperation with religion and strong protection for free exercise. Formal neutrality discounts religion as a basis either for conferring special benefits or for withholding generally available benefits. Positive neutrality attends to the practical effects of public policy, sometimes requiring an abandonment of nonestablishment in favor of policies that allow for greater protection for free exercise of religion. I argue that none of these forms of neutrality establishes impartiality regarding either religious belief or same-sex marriage. First, Michael McConnell's "disestablishment" approach to sexual orientation and same-sex marriage instantiates are neither neutrality nor civic equality. Second, while formal neutrality may render an establishment more inclusive, it may exclude those whose beliefs and practices are not deemed in accordance with public purposes. Third, although positive neutrality may remove burdens from same-sex couples whose conscientious convictions may impel them to marry, it may still favor some kinds of practices over others.